1995
DOI: 10.1144/gsl.qjegh.1995.028.s1.03
|View full text |Cite
|
Sign up to set email alerts
|

The Chalk as a karstic aquifer: evidence from a tracer test at Stanford Dingley, Berkshire, UK

Abstract: Karstic features such as swallow holes and dolines are the rule rather than the exception in the Chalk outcrop of southern England, particularly in the region of the Chalk/Tertiary boundary. Previous tracer tests at Bedhampton and Water End have indicated groundwater transport velocities of 2.2 and 5.5km/day. A recent tracer test at Stanford Dingley in Berkshire has indicated comparably high transport velocities in the Chalk: 5.8km/day for peak tracer concentration, and 6.8km/day for tracer breakthrough. In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…The Lambourn, for example, has an average stream gauge baseflow index (BFI) of 0.93, whilst the Pang has average BFI of 0.867 (Gustard et al, 1992). In addition to groundwater springs, there are several sink holes in both catchments, the most significant one being in the lower Pang catchment (Banks et al, 1995;Maurice et al, 2006). Significant impermeable Tertiary (Eocene) formations are also found in the lower Pang, including Reading Beds and London Clay.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The Lambourn, for example, has an average stream gauge baseflow index (BFI) of 0.93, whilst the Pang has average BFI of 0.867 (Gustard et al, 1992). In addition to groundwater springs, there are several sink holes in both catchments, the most significant one being in the lower Pang catchment (Banks et al, 1995;Maurice et al, 2006). Significant impermeable Tertiary (Eocene) formations are also found in the lower Pang, including Reading Beds and London Clay.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The Chalk is a porous fractured limestone that exhibits small-scale karstic features at the surface -sinking streams and dolines, plus an extensive dry valley network. Subsurface karst is also developed to some degree (Banks et al, 1995;MacDonald et al, 1998;Maurice et al, 2006;Worthington and Ford, 2009) but the influence this has on groundwater flow and contaminant transport remains poorly understood. It is not even certain whether an occurrence of dolines and sinking streams is a reliable indication that karst channels exist in the aquifer beneath them, nor how far such channels might extend where they are present.…”
Section: Introductionmentioning
confidence: 99%
“…More substantial cave networks have been described in Northern Ireland (Barnes, 1999), and geomorphological karst development in the French Chalk (solution features and caves) appears to be much more significant than in England (Rodet, 1991;Rodet et al, 2009). Codrington (1864), Harold (1937), Atkinson & Smith (1974), Rodet (1991), Banks et al (1995), Barnes (1999), Massei et al (2002Massei et al ( , 2006 and Maurice et al (2006) all report tracer tests on sinking streams in chalk with results that are summarised in Table 1. The earliest water tracing in the English Chalk was by Codrington (1864) who introduced dye into a stream sink in Wiltshire and reported its visible reappearance at a spring several kilometres away. Few details are given but the visible recovery suggests that attenuation was low.…”
Section: Introductionmentioning
confidence: 99%
“…Its ability to support major flows throughout the year demonstrates a large storage and slow response. On the other hand, historical tracer testing (Banks et al, 1995), confirmed by recent work of Maurice (Maurice et al, in press) has demonstrated travel times of the order of several kilometres per day. While tracer tests provide confirmation of certain flow connections, the contributing area of the Blue Pool has not been fully defined.…”
Section: Groundwater Flows In the Pang And Lambourn Catchmentsmentioning
confidence: 82%